Financial integration - growth nexus: a quantile regression analysis - Ibrahim, Saifuzzaman; Abdul Rahman, Mazlina; Wan Ngah, Wan Azman Saini; Mahamad Zakaria, Muhammad Farhan (Center for Economic Integration, Sejong Institution, Sejong University, 2016)
Our study aims to examine the role of economic development in moderating the relationship between international financial integration and economic growth, and we find that international financial integration has a positive impact on economic growth by and large. However, the growth impact of international financial integration does not exist in countries where economic development is too low or in highly developed countries. This suggests that policy makers, especially in developing countries, should ensure the presences of capabilities in order to gain from the financial market integration. The method involves a quantile regression technique on cross-sectional data of 73 countries.